Pairing and unpairing electron densities in organic systems: [1.1.1]Propellane case - Lobayan, Rosana Maria (2012)
We present a theoretical description of the case of the strained [1.1.1]propellane system by application of the local and nonlocal topological formalisms to the density decomposition into its effectively paired and unpaired contributions. The analysis is mainly focused on the nature of its carbon–carbon headbridge sequence and the existence of 2e–3c complex patterns of bonding. The results clearly indicate that the system only possess 2e–2c patterns, including a true carbon–carbon headbridge bond and no 3c–2e complex patterns of bonding appear.